1998
DOI: 10.1046/j.1365-2141.1998.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of patients with acute promyelocytic leukaemia with residual disease following ABMT performed in second CR using all‐trans retinoic acid

Abstract: Detection of residual disease after completion of therapy or following bone marrow transplantation (BMT) in patients with acute promyelocytic leukaemia (APL) predicts relapse and is associated with a poor prognosis. Here we describe the successful treatment of residual disease post‐transplant in APL using prolonged all‐trans retinoic acid (ATRA) therapy in two children in whom autologous BMT (ABMT) had been performed in second complete remission (CR). ATRA treatment was well tolerated and found to be beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
(25 reference statements)
2
13
0
Order By: Relevance
“…Significance of MRD for HCT SA Buckley et al retinoic acid in APL-its efficacy is suggested by case reports in this situation 92 -or tyrosine kinase inhibitors in BCR/ABL þ acute leukemias, and this approach is under active investigation. The validity of this approach was suggested by a prospective, multicenter study on 27 adults with BCR/ABL þ ALL who received imatinib upon MRD detection after AlloHCT.…”
Section: Mrd à Patientsmentioning
confidence: 99%
“…Significance of MRD for HCT SA Buckley et al retinoic acid in APL-its efficacy is suggested by case reports in this situation 92 -or tyrosine kinase inhibitors in BCR/ABL þ acute leukemias, and this approach is under active investigation. The validity of this approach was suggested by a prospective, multicenter study on 27 adults with BCR/ABL þ ALL who received imatinib upon MRD detection after AlloHCT.…”
Section: Mrd à Patientsmentioning
confidence: 99%
“…Due to the favorable prognosis with standard chemotherapy today allo-SCT is performed in these genetic subtypes only in case of relapse or poor response to therapy. [86][87][88] Molecular assessment in these rearrangements is helpful also after SCT, as stable remissions were associated in all analyzed patients with the CBFB-MYH11 89 or AML1-ETO subtypes 90 associated with the achievement of PCR negativity.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…A recent study suggests that early administration of salvage therapy at the time of molecular relapse is advantageous in APL. 41 Additional options for salvage therapy including arsenic trioxide, known as more potent than ATRA for inducing molecular remission, 40 could also probably be useful here, 42 as well as the use of ATRA therapy post-transplant 39 and new modalities of autologous SCT.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR of the PML/RAR␣ fusion gene has proved extremely useful for sensitive detection of minimal residual disease [36][37][38] and may predict relapse in APL patients in hematologic CR. 24,25,39 As a consequence, several investigators have adopted the term of molecular remission as a more advanced therapeutic goal in this disease. 40,41 In our study, preliminary results regarding detection of PML/RAR␣ by a RT-PCR assay after autologous PBSCt are encouraging and tend to confirm that autologous transplantation in APL achieving a second CR is likely to result in prolonged clinical and molecular remissions.…”
Section: Discussionmentioning
confidence: 99%